Konsep Persahabatan dengan non-Muslim dalam QS. Al-Mumtahanah Ayat 7-8 (Study Komparatif Tafsir Al-Misbah dan Kemenag RI) - Mujtahid; Ali Hasan Assidiqi (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
This study discusses the concept of friendship with Non-Muslims in QS al Mumtahanah verses 7-8 using the literature method with a qualitative descriptive approach and comparative analysis of two thematic interpretations, namely Muhammad Quraish Shihab's Tafsir Al-Misbah and the Tafsir of the Ministry of Religion of the Republic of Indonesia. The result is that it has the same strengthening of interpretation, the difference lies in the way of delivery where the Ministry of Religion tells a lot about related themes with a focus on various meanings with a complete story and is associated with the Indonesian context. Meanwhile, Tafsir Al-Misbah does not describe the story in full but only takes the point. However, in terms of meaning, both interpretations are equally clear and detailed starting from vocabulary, asbabun nuzul, related hadith, associated with other verses, and the meaning of the verses contained therein. So from this, the analysis obtained from the two Tafsirs, it is found that Al-Mumtahanah verse 7 confirms that Allah commands Muslims to accept a form of peace from their enemies, whether in the same family, the same tribe or still different religions or groups, so that they become united through life, and this is guaranteed by Allah that the friendship will occur. This is proven at this time in 2023, many countries including Indonesia have established the concept of friendship between Muslims and other religions without any differences.